Factors Influencing Patient Decisions to Initiate and Discontinue Subcutaneous Testosterone Pellets (Testopel) for Treatment of Hypogonadism. (16th July 2013) - Smith, Ryan P.; Khanna, Abhinav; Coward, Robert M.; Rajanahally, Saneal; Kovac, Jason R.; Gonzales, Marshall A.; Lipshultz, Larry I.
Abstract: Introduction: A variety of modalities for testosterone replacement therapy (TRT) are available, including topical gels, injections, and Testopel subcutaneous testosterone pellets (STP). STP are becoming more commonly utilized in the United States; however, patient preferences, expectations, and usage patterns regarding this therapy remain poorly characterized. Aim: To identify factors influencing patients' decisions to initiate or discontinue STP. Methods: A total of 175 men from an academic urology clinic who were currently using or who had previously used STP for hypogonadism received a 32‐item electronic survey. Main Outcome Measures: Assessment of the impact of convenience, efficacy, side effects, cost, and symptom relief on initiation and discontinuation of STP. Results: One hundred and thirteen men (64.6% response rate) of mean age 51.4 years who previously underwent a mean of 2.8 STP implant procedures completed the survey. Fifty‐nine (52.2%) and 40 (35.4%) men had switched to STP from topical gel and injection therapy, respectively, whereas 14 (12.4%) men initially started TRT with STP. Convenience (68.8%) was the most important factor in patients' decision to start STP, while cost of the previous form of TRT (14.7%) was least important. At the time of the survey, 32 men (28.3%) had discontinued STP therapy. Cost of therapy (50%) was the primary factor in discontinuing STP. There was no difference in serum testosterone levels between men who continued STP and those who discontinued therapy (642.8 vs. 629.0 ng/dL, P = 0.83). Overall, 68.1% of patients continued STP therapy at the time of survey completion. Conclusions: Convenience is the most important factor in a patient's decision to initiate STP; however, physician recommendation also plays a substantial role. Cost was the primary reason for discontinuation. Upon survey completion, greater than two‐thirds of respondents elected to continue STP therapy. STP are a viable treatment option for hypogonadal men seeking a convenient and efficacious alternative modality of TRT.Smith RP, Khanna A, Coward RM, Rajanahally S, Kovac JR, Gonzales MA, and Lipshultz LI. Factors influencing patient decisions to initiate and discontinue subcutaneous testosterone pellets (Testopel) for treatment of hypogonadism. J Sex Med 2013;10:2326–2333.